Macromolecular crystallography beamline X25 at the NSLS. (1st May 2014) - Héroux, Annie; Allaire, Marc; Buono, Richard; Cowan, Matthew L.; Dvorak, Joseph; Flaks, Leon; LaMarra, Steven; Myers, Stuart F.; Orville, Allen M.; Robinson, Howard H.; Roessler, Christian G.; Schneider, Dieter K.; et al.
<x xml:space="preserve">Abstract</x> Beamline X25 at the NSLS is one of the five beamlines dedicated to macromolecular crystallography operated by the Brookhaven National Laboratory Macromolecular Crystallography Research Resource group. This mini‐gap insertion‐device beamline has seen constant upgrades for the last seven years in order to achieve mini‐beam capability down to 20 µm × 20 µm. All major components beginning with the radiation source, and continuing along the beamline and its experimental hutch, have changed to produce a state‐of‐the‐art facility for the scientific community.